Sustainable Concreting: Optimization Modelling of the Strength Properties of Bio-Self Compacting Concrete Incorporating Sporosarcina Pasteurii, Calcined Clay and Limestone Powder - Taku, Kumator; Lawan, Adamu (Journal of Engineering Science, 2024)
Sustainable concreting is prerequisite for infrastructural development in developing countries so as to meet up with the sustainable development goal of adequate mass housing and other critical infrastructure. Thus, research is ever ongoing aimed at developing cheaper and more durable concrete via the incorporation of bio-based by-products in concrete to improve its properties, as well as optimizing the quantities of these secondary materials for maximum and optimal concrete production. One such revolutionary concrete that is yet to find full application in the developing world is self-compacting concrete, because of the cost and attendant environmental effects. There is thus a need to arrive at optimal materials quantities that can maximize concrete properties without recourse to many trial and error experimentations that are both time and resources consuming. The application of modelling tools in concrete technology aids in the optimization of concrete constituents for optimal self-compacting concrete performance. This research uses optimization techniques to optimize the bacteria dosage as well as model the Compressive and Tensile strength properties of a calcined clay and Limestone powder blended ternary self-compacting concrete using sporosarcina pasteurii as Microbial induced calcite precipitation agent and calcium lactate as nutrient source. The Bacteria was incorporated into the concrete at a bacterial content of 1.5x108cfu/ml, 1.2x10 cfu/ml and 2.4x109cfu/ml corresponding to the McFarland turbidity scale of 0.5, 4 and 8 while the nutrient (calcium lactate) content was 0.5, 1.0 and 2.0% by weight of cement for each bacterial content. The Compressive strength and tensile strengths at 28 days were determined and the results used for both the model development, strength optimization and model validation, with the strengths as the dependent variable (y) and the bacterial content corresponding to a McFarland scale of and calcium lactate content as the independent variables, X1 and X2 respectively. The results show an improvement in the compressive strength from 32N/mm2 to 45.2N/mm2 at the optimal bacterial and nutrient content of 1.2x10 cfu/ml and 0.5% respectively, and tensile strength from 4.01N/mm2 to 5.0N/mm2. Also, the non-linear regression models proved adequate for optimizing the bacterial content for optimal self-compacting concrete performance. Journal of Engineering Science 15(1), 2024, 11-19